Whether B-Schools Care Spencer & Spencer’s Workplace Competency Framework in the 21st Century? -Revalidating through Reliability - Prof. Arup Barman, Karan Das (International Journal of Advanced Science and Technology, 2020)
In 21stcentury, all organizations are talking in terms of competence. Gone are the days when people used to talk in terms of skill sets, which would make their organizations competitive. There has been a shift in the strategy of the organizations. Now they believe in excelling but not on just competing. This intensifying competition for competitive advantage in business, have led to a surge of an intensifying competition known as ‘the global war for talent’ where the business leaders seek to achieve the competitive advantage through an army of the best and brightest global workforce in the industry.